Sedimentary facies and stratigraphy of the Palaeocene to middle Eocene Belaga formation Sibu, Sarawak / Galih Yudha Kuswandaru - Galih Yudha , Kuswandaru (2017)
A detailed facies analysis is presented for the Paleocene to middle Eocene Kapit and Pelagus members, Belaga Formation, exposed around Sibu, Sarawak, Malaysia. The Belaga Formation is compared to the West Crocker Formation of onshore Sabah and also the offshore, Neogene, hydrocarbon-bearing reservoirs of NW Sabah, in order to understand the variations in submarine channel, levee and lobe architecture in the Tertiary deepwater systems of Borneo. Facies in the Belaga Formation are characterised by thin to thick bedded turbidites, debrites and associated hemipelagic/pelagic mudstone. The facies are arranged into 6 types of facies associations. Channel-fill facies associations display channel geometries and are composed of interbedded debrites, turbidites and mudstone. The levee facies association comprises stacked, dm to m-thick, thinning upward cycles of interbedded turbidites, debrites and mudstone. The lobe (channel mouth) facies association forms thickening upward successions of interbedded high density turbidites, debrites, hybrid beds and mudstone. The lobe (fringe) facies association forms thinning upward successions comprising debrites with interbedded mudstone and thin turbidites. The basin plain facies association forms thick successions of interbedded mudstone and thin bedded turbidites. The slump facies association is composed of deformed levee deposits. The Belaga Formation is interpreted to represent deepwater deposits of a mud-rich, basin floor submarine fan depositional system, comprising elements of leveed channel systems and associated frontal splay-type lobes, which represent change in relative sea change. Tens of meters thick successions of lobe (channel mouth) deposits gradually overlain by channel fill deposits, or lobe (fringe) deposits overlain by thick levee deposits are interpreted as representing lobe progradation. Thick successions of interbedded levee and channel fill deposits are interpreted as representing leveed channel successions. The West Crocker Formation of NW Sabah also comprises leveed channel and lobe elements, but is a sand-rich system. iii The Neogene deepwater deposits of offshore NW Sabah also share the same facies architecture with the Belaga Formation, but individual fans can be either sand- or mud-rich. The Belaga Formation and Neogene Sabah systems all share depositional trends which are perpendicular to the regional SW-NE structural trend of Borneo. However, the major difference is the common occurrence of laterally extensive mass transport deposits (MTDs) offshore NW Sabah, which are rare in the Belaga Formation, suggesting less frequent tectonic disturbance and/or lower sediment supply.